A Relationship between Calcium Deposit Size with the Pain Intensity on The Patients with Calcified Tendinitis in The Rotator Cuff - Indri Wijayanti; I Nyoman Murdana; Tirza Z. Tamin (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Calcified tendeinitis is a disease characterized by calcification of multifocal cells mediated byliving tissue. Calcified tendeinitis may occur due to the collection of calcium in the pouch of supraspinatustendon or may spread between rotator cuff muscle fibers and bursa. This deposit may or may not cause pain ofdiscomfort. The study aim is to determine the correlation of calcium deposit size to the pain intensity in patientswith calcified tendinotis.Methods: A cross-sectional study, on subjects, were diagnosed with calcified tendinitis rotator cuff bymusculoskeletal ultrasonography examination.Results: The twenty subjects, aged 50-70 years old, No significant correlations were found between calciumdeposit size with the pain intensity using VAS, r=0.238, p=0.32.Conclusion. The size of the calcium deposit has not correlated with the pain intensity in rotator cuff calcifiedtendinitis patients. But further research is needed whether the location and form of calcium deposits affect thepain intensity in calcified tendinitis rotator cuff patients.Keywords: calcified tendinitis; calcium deposit size; pain intensity.